Non-communicable disease surveillance in India using Geographical Information System-An experience from Punjab - Saleem, Sheikh Mohd; Aggarwal, Chaitnya; Bera, Om Prakash; Rana, Radhika; Singh, Gurmandeep; Bhattacharya, Sudip (Indian Journal of Community Health, 2021)
"Geographic information system (GIS) collects various kinds of data based on the geographic relationship across space." Data in GIS is stored to visualize, analyze, and interpret geographic data to learn about an area, an ongoing project, site planning, business, health economics and health-related surveys and information. GIS has evolved from ancient disease maps to 3D digital maps and continues to grow even today. The visual-spatial mapping of the data has given us an insight into different diseases ranging from diarrhea, pneumonia to non-communicable diseases like diabetes mellitus, hypertension, cardiovascular diseases, or risk factors like obesity, being overweight, etc. All in a while, this information has highlighted health-related issues and knowledge about these in a contemporary manner worldwide. Researchers, scientists, and administrators use GIS for research project planning, execution, and disease management. Cases of diseases in a specific area or region, the number of hospitals, roads, waterways, and health catchment areas are examples of spatially referenced data that can be captured and easily presented using GIS. Currently, we are facing an epidemic of non-communicable diseases, and a powerful tool like GIS can be used efficiently in such a situation. GIS can provide a powerful and robust framework for effectively monitoring and identifying the leading cause behind such diseases. GIS, which provides a spatial viewpoint regarding the disease spectrum, pattern, and distribution, is of particular importance in this area and helps better understand disease transmission dynamics and spatial determinants. The use of GIS in public health will be a practical approach for surveillance, monitoring, planning, optimization, and service delivery of health resources to the people at large. The GIS platform can link environmental and spatial information with the disease itself, which makes it an asset in disease control progression all over the globe.